Identification and quantification of flavonoids and hydroxycinnamic acids in yellow wood anemone (Anemone ranunculoides L.) by UHPLC-DAD-HESI/MS analysis - A. N. Luferov; N. V. Bobkova; D. O. Bokov; M. N. Rodin; E. V. Sergunova; T. Yu. Kovaleva; T. D. Rendyuk; A. V. Strelyaeva; A. M. Antsyshkina; T. V. Prostodusheva; S. G. Zaichikova; V. M. Baeva; et al. (Разработка и регистрация лекарственных средств)
Introduction. Yellow wood anemone (Anemone ranunculoides L.) is a herbaceous perennial. This plant grows in the European parts of Russia, Ciscaucasia, Siberia, Central Europe and other regions. It has many different pharmacological activities: immunomodulatory, sedative, anti-inflammatory, antitoxic, diuretic, antibacterial, antioxidant, antitumor and antirheumatic activity. These various effects are due to their biologically active compounds, which include ephemeroids, protoanemonin, saponins, tannins, resins, ascorbic acid, ranunculin, oils lipids and triterpene glycosides. As to phenolic compounds, currently there is no sufficient information on flavonoids and hydroxycinnamic acids (HCAs) profiles in different species of genus Anemone. Because these groups of compounds are quite specific for yellow wood anemone, their detailed study seems to be relevant.Aim. The objective of this research is to identify and quantify flavonoids, HCAs, and their conjugates in Yellow wood anemone leaves, flowers and rhizomes with roots.Materials and methods. The identification was carried out by using ultra-high-performance liquid chromatography with diode array and electrospray ionization-mass spectrometric detection (UHPLC–DAD–ESI-MS) with quantification of individual compounds by external calibration method.Results and discussion. Among the 47 compounds, 30 flavonoids and 17 derivatives of HCAs were detected. Quercetin glycosides were found to be the major flavonoids in aerial parts whereas chalcone glycosides – in underground parts. The major HCA in rhizomes with roots was feruloyltartaric acid (1.18 mg/g) whereas chlorogenic acid was predominant in leaves and flowers (8.68 mg/g and 2.62 mg/g accordingly). The total content of phenolic compounds was estimated at 60 mg/g on a dry weight basis.Conclusion. As a result of the research a detailed profile of flavonoids and HCAs acids of anemon was described. The data obtained can serve to identify this species in the standardization of medicinal plant materials and taxonomic studies.